A chromosome-level reference genome for the giant pink sea star, Pisaster brevispinus, a species severely impacted by wasting. (30th November 2022) - DeBiasse, Melissa B; Schiebelhut, Lauren M; Escalona, Merly; Beraut, Eric; Fairbairn, Colin; Marimuthu, Mohan P A; Nguyen, Oanh; Sahasrabudhe, Ruta; Dawson, Michael N
Abstract: Efforts to protect the ecologically and economically significant California Current Ecosystem from global change will greatly benefit from data about patterns of local adaptation and population connectivity. To facilitate that work, we present a reference-quality genome for the giant pink sea star, Pisaster brevispinus, a species of ecological importance along the Pacific west coast of North America that has been heavily impacted by environmental change and disease. We used Pacific Biosciences HiFi long sequencing reads and Dovetail Omni-C proximity reads to generate a highly contiguous genome assembly of 550 Mb in length. The assembly contains 127 scaffolds with a contig N50 of 4.6 Mb and a scaffold N50 of 21.4 Mb; the BUSCO completeness score is 98.70%. The P. brevispinus genome assembly is comparable to the genome of the congener species P. ochraceus in size and completeness. Both Pisaster assemblies are consistent with previously published karyotyping results showing sea star genomes are organized into 22 autosomes. The reference genome for P. brevispinus is an important first step toward the goal of producing a comprehensive, population genomics view of ecological and evolutionary processes along the California coast. This resource will help scientists, managers, and policy makers in their task of understanding and protecting critical coastal regions from the impacts of global change.